Development of Ni-based redox catalysts for chemical looping processes - Huang, Jijiang (2019)
Chemical looping concept describes a class of processes that uncouples an overall homogeneous reaction into heterogeneous sub-reactions, using a solid intermediate, namely oxygen carrier or redox catalyst shuttling between the sub-reactions to transfer the reaction species. Take chemical looping combustion (CLC) as an example, the fuel and air will react with the oxidized and reduced oxygen carrier in separated gas stages or reactors, generating a concentrated CO2 stream after H2O removal by condensation during the fuel combustion. The thermodynamic fuel conversion efficiency increases but the NOx formation is hindered due to the relative low working temperatures compared with the traditional single-stage combustion. Thus, CLC offers the benefits of fuel combustion with inherent CO2 capture and significantly reduced NOx formation over conventional combustion. The formulation and phase interactions in the oxygen carriers play important roles in determining the activity of the lattice oxygen, so as the performance of the oxygen carriers. In Chapter 4, NiO-MgO-Al2O3 oxygen carriers were synthesized using layered double hydroxides (LDH) as precursors to facilitate the formation of molecular level dispersion of cations in the resulting oxygen carriers after calcination. The performance of the synthesized oxygen carriers was investigated over 100 chemical looping cycles of 5 vol.% H2/N2 reduction and 5 vol.% O2/N2 oxidation. The morphology and phase composition of the fresh and spent oxygen carriers were characterized by SEM, XRD and TPR. Rietveld refinement of the XRD patterns and TPR confirmed the presence of halite (MgO-NiO) and spinel (MgAl2O4-NiAl2O4) solid solutions, the composition of which changed over cycles and determined the cycle behavior of the oxygen carriers. Using CH4 as the fuel, NiO performs poorly in CLC due to the severe carbon deposition from CH4 decomposition catalyzed by the reduced Ni particles. The performance may be modified by CuO which provides selective lattice oxygen for CLC. Chapter 5 reports a systematic investigation of NiO-CuO-Al2O3 mixed oxide oxygen carriers over chemical looping oxidation of CH4. The oxygen carriers were prepared from Ni/Cu/Al LDH precursors, which were synthesized via the hydrothermal reactions using urea as the precipitant. The solids’ compositions were analyzed by a set of complementary experimental techniques (SXRD, TGA, TPR). It was found that the formation of NiAl2O4 is favored over that of CuAl2O4 after calcinations at 1000 oC. The results also suggest that the mixing of NiO and CuO leads to enhanced lattice oxygen activity in both oxides. However, the lattice oxygen activity in the (Ni,Cu)Al2O4 spinel was reduced due to the formation of solid solution Ni1-xCuxAl2O4, which appears to be an excellent retardant for carbon deposition. The findings in this study are useful to the design of high performance oxygen carrier that exploits the phase interactions in the Ni-Cu-Al2O3 system. In traditional steam reforming of methane (SRM), with CH4 and steam co-fed into the reactor, the selectivity to CO and H2 are thermodynamically limited in the presence of water gas shift reaction. In Chapter 6, a series of Ni-Fe redox catalysts with varying Ni/Fe ratios were designed and prepared by co-precipitation, which could selectively convert CH4 to syngas via chemical looping steam reforming coupled with catalytic CH4 decomposition. Carbon deposit in the CH4 reduction stage was selectively gasified to syngas in the following oxidation with hot steam, so that the overall selectivity to CO was dramatically enhanced in the chemical looping scheme. The optimized redox catalyst with equimolar Ni and Fe could achieve high CH4 conversion up to 97.5% and CO selectivity up to 92.9% with excellent stability at 900 oC, with productivity of 9.6 and 29.0 mol per kg catalyst per cycle for CO and H2, respectively.